Desain Lanskap Lapangan Golf Berbasis Fungsi Ekologis - Syach Fahreza; Alfred Jansen Sutrisno (Jurnal Lanskap Indonesia, 2022)
The golf course landscape is one form of sports area that can be a buffer zone between urban and rural areas. The golf course landscape functions as an area to absorb CO2 in the atmosphere, a windbreaker as well as a habitat for birds. The purpose of this research is to produce an ecologically based golf course landscape plan and design. The planning process includes site inventory surveys, site data analysis, design concept creation, golf course design development, and design development. Stages of site analysis using descriptive methods on the biophysical and physical components of the site. Meanwhile, the data analysis used the stored carbon analysis method is a allometric equation. The results show that in planning the golf course landscape, the landscape is divided into three spaces, namely the game area, maintenance area and service area. Then, landscape planning also determines the proposed contour, proposed drainage, and vegetation selection. The results of the planning are used to design the landscape, where the planting design is determined based on the composition of the vegetation that produces the highest stored carbon, which consists of grass, herbs, shrubs and trees. Then, the selection of vegetation that can bring birds and vegetation that can break the wind. The forms of planning and designing the golf course landscape are in the form of proposed contour drawings, proposed drainage, spatial concepts and three-dimensional visualization of the golf course landscape.